Konsep Kasih Sayang dan Empati dalam Hadits Nabi Muhammad Perspektif Pendidikan Islam - Ngatmin Abbas; Uzlifatul Jannah; Fitrianisa Sri Utami; Siti Marhamah; Aisyah Anna Safitri (Medan Resource Center, 2025)
This study explores the concepts of love and empathy in Islamic education through hadith perspectives, focusing on understanding their profound role in supporting learning processes and interpersonal relationships. Employing a qualitative descriptive approach, the research analyzes hadiths containing messages of love and empathy to identify and categorize key insights. The findings underscore the critical importance of love and empathy as essential elements in educational practice, particularly within Islamic educational frameworks that prioritize noble character development. These values contribute to creating supportive and conducive learning environments where students feel genuinely valued and understood. By fostering mutual respect, enhancing learning effectiveness, and strengthening social connections, love and empathy emerge as transformative principles that fundamentally shape students' character and personal growth. The research ultimately argues that integrating these compassionate values into Islamic education is not merely a pedagogical strategy but a fundamental approach to nurturing holistic, emotionally intelligent, and morally grounded individuals.